Rainfall-Runoff Modeling for Challawa and Jakara Catchment Areas of Kano City, Nigeria. - Mohammed, A.; Dan’Azumi, S.; Modibbo, A. A.; Adamu, A. A.; Ibrahim, Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
For the past decade, the magnitude and frequency of rainfall that resulted into flooding of Kano city have been relatively high and there is need to manage the flood in order to safe life and properties. This research aimed at generating Challawa and Jakara catchment areas runoff for hydrological applications. The two catchments were first delineated and their basic physical properties were extracted from processed 30 m x 30 m Digital Elevation Models (DEMs) of the respective watershed. Basin models of the watersheds were imported from ArcGIS 10.7 to Hydrologic Engineering Center – Hydrologic Modelling System (HEC-HMS) environment, the meteorological models were developed in HEC-HMS with rainfall data and control specifications assigned which defined the period and time step of the simulation run. SCS-Curve Number, Unit Hydrograph and Muskingum methods were used for estimation of loss, runoff and flow routing respectively. The rainfall-runoff simulations were carried out for 31 years of maximum daily rainfall record (1988 – 2018). The simulated flow rate obtained can be used for further hydrological analysis such as flood frequency analysis and in design of safe and economical drainage and flood control facilities or in maintenance of culverts, sewers, bridges and roads for Jakara and Challawa catchment areas. It is recommended that; the catchment areas be gauged while further research should be conducted on the quality of the simulated flow obtained.